Housing loan evaluation system using regression analysis - Tay, Chze Huat (2011)
Normally,the housing loan companies have to do the same calculations for all of their customers'loan applications. This manual system is troublesome and time consuming.Apart from that,the process of approving a housing loan is done by human using logical reasoning and a few surface calculations.This method does not involve every factor that is related, and some major ones may be overlooked.At the present,the use of factor analysis is widely use in help to lessen burden in making analysis and prediction.Therefore, Housing Loan Evaluation System is developed to suits the need of the loan companies in making analysis generally. This system takes a list of factors related to the loan as inputs.Then,it filters out and sort them according to the importance level. After that,the applied statistics method are use to make an evaluation and from the result,the company can choose to approve or not to approve the loan application.